DISTRIBUTION OF POTASSIUM FRACTIONS IN DIFFERENT LAND USE SYSTEMS IN SOME SOIL SERIES OF WEST BENGAL - SANATAN BEHERA; A. KRISHNA CHAITANYA,; S. K. GHOSH; P. K. PATRA (The Bioscan, 2015)
Soil samples were collected from three soil depths viz., 0-15, 15-30 and 30-45 cm, under six ecosystems of two soil series from Paschim Medinipur district under Red and Laterite Zone of West Bengal to study the distribution of potassium forms. Irrespective of soil series and depth the sequential order of different potassium fractions were non-exchangeble K > available K > exchangeble K > water soluble K. All K fractions were higher in surface layer than that subsurface layer. In Jhargram soil series water soluble K ranges from 1.01 to 1.31, exchangeable K 5.46 to 7.89, while available K is more in fallow lands. Irrespective of land use systems, available and exchangeable K were strongly positively correlated (r=0.990). In saripabasa soil series water soluble K ranges from 2.42 to 3.54, exchangeable K 15.67 to 54.22, while available K is more in low land rice ecosystem. Irrespective of land use systems, available and exchangeable K were strongly positively correlated (r=1.00), available K was positively correlated with OC (r=0.623), water soluble K (r=0.459).